2020
DOI: 10.3390/app10041218
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology of Interactive Motion Facades Design through Parametric Strategies

Abstract: Interactive facades are dynamic in the translation of space in architecture, especially in the aspects of aesthetics, sustainability, adaptation to the environment, and data relay through the medium of light, motion, and embedded technology. The design of interactive facades is complicated and it requires time and effort in the comprehension of the internal functions of the facade from the conceptual stage to occupancy. The existing process of modeling the experimental level of interactive facades through mock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For Bui et al (2020) and Loonen (2018), responsiveness means changing properties over time to decrease energy consumption. Other terms are adaptive (Lee;Cho;Jo, 2021), interactive (Panya;Choo, 2020), and interchangeable.…”
Section: Responsive Typologymentioning
confidence: 99%
“…For Bui et al (2020) and Loonen (2018), responsiveness means changing properties over time to decrease energy consumption. Other terms are adaptive (Lee;Cho;Jo, 2021), interactive (Panya;Choo, 2020), and interchangeable.…”
Section: Responsive Typologymentioning
confidence: 99%
“…Therefore, inaccurate results might be obtained when assessing their performance and applicability in the long term (Tabadkani et al 2020c). Since the development of AF by many researchers has increased significantly in recent years (Elzeyadi 2017;Hosseini et al 2019b;Böke et al 2020;Bui et al 2020;Panya et al 2020;Shi et al 2020), it is essential to find an alternative approach that requires less computation knowledge and that is less time consuming to predict their performance efficiently during the early design stages.…”
Section: Adaptive Façade Overviewmentioning
confidence: 99%
“…Software such as Revit/Dynamo and Rhinoceros/Grasshopper provide great potential for kinetic façade design when used with building performance simulation methods [3]. Panya et al [24] summarized some parametric design tools used in the field of architecture. The literature review identified several studies on kinetic façade design with the application of parametric design tools and energy efficiency and daylighting evaluations.…”
Section: Evaluation and Comparison Of Decision Support Toolsmentioning
confidence: 99%